2020
DOI: 10.1021/acssensors.0c01908
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Flexible SERS Sensor on a Fixate Gel Pad: Capturing, Derivation, and Selective Picogram Indirect Detection of Explosive 2,2′,4,4′,6,6′-Hexanitrostilbene

Abstract: 2,2′,4,4′,6,6′-Hexanitrostilbene (HNS) is an explosive with better explosion performance than the well-known 2,4,6trinitrotoluene (TNT). Surprisingly, unlike other nitroaromatic explosives, there are limited reports regarding the detection of the HNS, let alone sensing reports on surface residues. In this work, a multifunctional flexible SERS sensor was proposed for the indirect detection of HNS based on the transparent fixate gel pads. The sticky and flexible gel pad can effectively collect any HNS surface re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 45 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…[95][96][97] For example, Fan, et al demonstrated a flexible SERS sensor for rapid and in-field detection of the surface residues of a commonly used explosive, 2,2',4,4',6,6'hexanitrostilbene (HNS). 98 More specifically, the authors showed that commercially available sticky and flexible gel pads composed mainly of polyurethane could be used to extract HNS from complex sample surfaces through the formation of Meisenheimer-alike complexes between HNS and the amine moieties on the surface of the gel substrate which are visually identifiable as orange taints. Depositing aggregated citratereduced Ag nanoparticles directly onto the surface of the orange taints generated intense SERS signals of the analytesubstrate complexes which allowed indirect detection of HNS to be achieved.…”
Section: Deposition Of Preformed Plasmonic Nanoparticlesmentioning
confidence: 99%
“…[95][96][97] For example, Fan, et al demonstrated a flexible SERS sensor for rapid and in-field detection of the surface residues of a commonly used explosive, 2,2',4,4',6,6'hexanitrostilbene (HNS). 98 More specifically, the authors showed that commercially available sticky and flexible gel pads composed mainly of polyurethane could be used to extract HNS from complex sample surfaces through the formation of Meisenheimer-alike complexes between HNS and the amine moieties on the surface of the gel substrate which are visually identifiable as orange taints. Depositing aggregated citratereduced Ag nanoparticles directly onto the surface of the orange taints generated intense SERS signals of the analytesubstrate complexes which allowed indirect detection of HNS to be achieved.…”
Section: Deposition Of Preformed Plasmonic Nanoparticlesmentioning
confidence: 99%
“…According to a previous report, [ 13 ] the concentration of halide ions could also affect the SERS signal of the analyte. Hence, the concentration of Br − was then optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Silver nitrate was reduced with sodium citrate to obtain Ag NPs according to our previous reports. [ 13,24 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart hydrogels have been much concerned due to the stimulus responsive behaviors to the environmental triggers. [ 1–4 ] In order to develop their potential applications in various fields, such as wearable electronic devices, [ 5–8 ] flexible sensors, [ 9–13 ] biological drug‐carrying, [ 14–18 ] and storage cells, [ 19–21 ] it is very significant to adjust their sol–gel transition temperature ( T gel ). Their special swelling behavior at certain lower or upper critical solution temperatures (LCST or UCST) has promoted the applications as anti‐fogging and anti‐icing materials through delaying the coalescence of condensed drops and inhibiting ice nucleation and/or growth, respectively.…”
Section: Introductionmentioning
confidence: 99%